2021
DOI: 10.31661/jbpe.v0i0.2102-1284
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Metal Artifact Reduction Algorithm of Cone-Beam Computed Tomography for Detection of Fenestration and Dehiscence around Dental Implants

Abstract: Background: Beam hardening and scattering artifacts from high-density objects such as dental implants adversely affect the image quality and subsequently the detection of fenestration or dehiscence around dental implants. Objective: This study aimed to assess the efficacy of metal artifact reduction (MAR) algorithm of two cone-beam computed tomography (CBCT) systems for detection of peri-implant fenestration and dehiscence. Material and Methods: … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
3
2
1
Order By: Relevance
“…This is in accordance with the present study, in which, DMFR showed a higher agreement with the correct diagnosis, which can be attributed to their higher degree of experience and training for this task. Salemi et al, 2021, showed, for two experienced radiologists, a poor to moderate agreement with MAR ON and good to excellent agreement with MAR OFF, which is in accordance with the results found in this study. Fontenele et al, 2021, involving three oral radiologists, found that intra‐ and inter‐examiner agreement ranged from slight (weighted kappa = 0.10 and 0.13 respectively) to substantial (weighted kappa = 0.64 and 0.69 respectively) in the detection of buccal and lingual peri‐implant dehiscences.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in accordance with the present study, in which, DMFR showed a higher agreement with the correct diagnosis, which can be attributed to their higher degree of experience and training for this task. Salemi et al, 2021, showed, for two experienced radiologists, a poor to moderate agreement with MAR ON and good to excellent agreement with MAR OFF, which is in accordance with the results found in this study. Fontenele et al, 2021, involving three oral radiologists, found that intra‐ and inter‐examiner agreement ranged from slight (weighted kappa = 0.10 and 0.13 respectively) to substantial (weighted kappa = 0.64 and 0.69 respectively) in the detection of buccal and lingual peri‐implant dehiscences.…”
Section: Discussionsupporting
confidence: 92%
“…Comparing our results with diagnostic studies on MAR involving dental implants, Salemi et al, 2021 found that sensitivity, specificity and accuracy of diagnosing fenestration and dehiscence were higher with MAR OFF for both CBCT equipment used. Similarly, De‐Azevedo‐Vaz et al, 2016 found no improvement for the same diagnostic task when using MAR and Fontenele et al, 2022, found no influence of MAR and kV on the diagnosis of buccal and lingual peri‐implant dehiscence for titanium and zirconia implants.…”
Section: Discussionsupporting
confidence: 64%
“…In the current study, when MAR tool was applied, the AUC values and the diagnostic values revealed that peri-implant fenestrations were more correctly diagnosed than peri-implant dehiscences. Similar findings have been reported by de-Azevedo-Vaz et al [ 2 , 5 ], Sheikhi et al [ 23 ], and Salemi et al [ 26 ], and they explained these findings by claiming that as dehiscence has just an inferior border, it is more difficult to identify than fenestration, which has both superior and inferior borders.…”
Section: Discussionsupporting
confidence: 86%
“…After that, the bone blocks were coated with a 1.5 mm layer of pink wax to mimic the soft tissue surrounding the alveolar bone and to maintain an equivalent x-ray beam attenuation (Fig. 2 ) [ 3 , 26 , 27 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have observed MAR to be effective in reducing implant-induced artifacts [ 10 , 11 , 15 , 17 , 19 21 , 27 , 29 , 32 ], whereas some reported MAR ineffective [ 5 7 , 9 , 13 , 22 , 24 , 25 , 28 ]. According to [ 26 ], implant material affects MAR efficacy.…”
Section: Resultsmentioning
confidence: 99%